2013
DOI: 10.3109/0886022x.2013.808957
|View full text |Cite
|
Sign up to set email alerts
|

Role of CIP4 in high glucose induced epithelial--mesenchymal transition of rat peritoneal mesothelial cells

Abstract: This study shows that CIP4 promotes high glucose-induced EMT through PI3K-Akt signaling pathway in RPMCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…It has been shown that CIP4 promotes TGF-β1-induced EMT of renal proximal tubular epithelial cells [19] and mediates high glucose-induced EMT through PI3K-Akt signaling pathway in rat peritoneal mesothelial cells [20]. Moreover, knockdown of CIP4 strongly increases the formation of tubular E-cadherin vesicles at adherens junctions [21].…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that CIP4 promotes TGF-β1-induced EMT of renal proximal tubular epithelial cells [19] and mediates high glucose-induced EMT through PI3K-Akt signaling pathway in rat peritoneal mesothelial cells [20]. Moreover, knockdown of CIP4 strongly increases the formation of tubular E-cadherin vesicles at adherens junctions [21].…”
Section: Resultsmentioning
confidence: 99%
“…CIP4 is overexpressed in normal epithelial cells undergoing the epithelial-mesenchymal transition (Zhang et al, 2013). CIP4 is also overexpressed in osteosarcoma (Koshkina et al, 2013), in chronic lymphocytic leukemia (Malet-Engra et al, 2013), in non-small cell lung cancer (Truesdell et al, 2014) and in a subset of invasive breast cancer cells (Pichot et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CIP4 acts downstream of cdc42 activation to promote membrane deformation, vesicle scission and actin polymerization (Fricke et al, 2009), thus participating in endocytosis (Leibfried et al, 2008;Hartig et al, 2009;Feng et al, 2010), and in the formation of lamellapodial protrusions (Saengsawang et al, 2012) and pro-invasive invadopodia structures (Pichot et al, 2010;Hu et al, 2011). Regarding cell migration, CIP4 is upregulated during epithelial-mesenchymal transition (Zhang et al, 2013) and has been reported to be essential for the development of metastatic properties in different types of cancer cells (Pichot et al, 2010;Truesdell et al, 2014;Rolland et al, 2014;Koshkina et al, 2013). Although most studies point to its involvement in the formation of membrane structures that are necessary for cell migration, the actual mechanism by which CIP4 plays a central role in the acquisition of migratory properties has not been clarified yet.…”
Section: Introductionmentioning
confidence: 99%
“…HG activates PI3K-Akt-mTOR pathway PI3K/Akt pathway is one of the most well known pathways upstream to mTOR and its activation has been implicated as an important mechanism in HGinduced EMT [36][37][38]. To further understand the underlying mechanism, we examined whether HG activated the PI3K-Akt-mTOR signaling pathway in RPMCs.…”
Section: Rapamycin Inhibits Rpmc Migration Enhanced By Hgmentioning
confidence: 99%